Urgensi Partisipasi Masyarakat dalam Public Governance di Indonesia - Ni Wayan Desi Budha Jayanti (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2023)
Public participation in public governance has become a major issue in Indonesian governance. Public governance is defined as a concept that represents the government's ability to assist citizens in an inclusive, non-discriminatory manner, and provide individual satisfaction and prosperity for the people. Society is considered the main force in driving service quality and e-government implementation. In Indonesia, good public governance has been the focus of attention since 1999. However, public participation in public governance is often ignored by the government, so it is only considered a mere formality, which can cause tension and disharmony in public governance. This study aims to determine and analyze the urgency of public participation in public governance in Indonesia. This type of research is the SLR (Systematic Literature Review) method with a qualitative approach. Data sources are obtained from related journals through a literature review. The results of this study indicate that public participation in public governance in Indonesia is urgent because it can produce decisions or policies that are in accordance with the needs of the community, realize the success of development in Indonesia, effectively increase transparency, accountability, and compliance with the law and can realize ideal popular sovereignty.